Outcomes and cost implications of microvascular reconstructions of the head and neck. Issue 4 (9th February 2019) - Sweeny, Larissa; Rosenthal, Eben L.; Light, Tyler; Grayson, Jessica; Petrisor, Daniel; Troob, Scott H.; Greene, Benjamin J.; Carroll, William R.; Wax, Mark K.
Abstract: Background: Critical review of current head and neck reconstructive practices as related to free flap donor sites and their impact on clinical outcomes and cost. Methods: Retrospective multicenter review of free tissue transfer reconstruction of head and neck defects ( n = 1315). Variables reviewed: defect, indication, T classification, operative duration, and complications. A convenience sample was selected for analysis of overall (operative and inpatient admission) charges per hospitalization ( n = 400). Results: Mean charges of hospitalization by donor tissue: radial forearm free flap (RFFF) 127 636 ( n = 183), osteocutaneous RFFF (OCRFFF) 125 456 ( n = 70), anterior lateral thigh 133 781 ( n = 54), fibula 140 747 ( n = 42), latissimus 208 890 ( n = 24), rectus 169 637 ( n = 18), scapula 128 712 ( n = 4), and ulna 110 716 ( n = 5; P = .16). Mean operative times for malignant lesions stratified by T classification: 6.9 hours (±25 minutes) for T1, 7.0 hours (±16 minutes) for T2, 7.3 hours (±17 minutes) for T3, and 7.8 hours (±11 minutes) for T4 ( P < .0001). Complications correlated with differences in mean charges: minor surgical (123 720), medical (216 387), and major surgical (169 821; P < .001). Operations for advanced malignant lesions had higher mean charges: T1 lesions (106 506) compared to T2/T3 lesions (133 080; P = .03) and T4 lesions (142 183; P = .02). On multivariate analysis, the length of stay, operative duration, and type a postoperative complication were factors affecting overall charges for the hospitalization ( P < .018). Conclusion: Conclusion: The RFFF and OCRFFF had the lowest complication rates, length of hospitalization, duration of operation, and mean charges of hospitalization. Advanced stage malignant disease correlated with increased hospitalization length, operative time, and complication rates resulting in higher hospitalization charges.